Motivation of Personnel in a Healthcare Company - Ilgunov, Artur; Khutter, Matvei (Jyväskylän ammattikorkeakoulu, 2016)
For years, the concept of motivation has been a popular topic of discussion among various research-ers and practitioners. In present days, managers are continuously challenged to perceive, and in fact present, a strong performance of their subsidiaries and departments. The following thesis explored the concept of motivation. The main aim of this research was to exam-ine strategies used by managers in order to motivate employees, as well as to examine the current level of motivation of higher medical personnel and determine whether they are motivated or not. Additionally, it was questioned what kind of incentives are perceived positively by doctors. The moti-vation strategy was examined on the basis of the goal-setting theory, created by Edwin Locke. This study was assigned by Kivach – a healthcare clinic located in Karelian region in Russia. As a clinic providing high-quality health services, Kivach is very concerned about their employees’ motivation and satisfaction with the overall working conditions. That is why there was a need for an examination of the present motivational level of the Kivach personnel, working conditions and motivational tech-niques as applied by the managers in Kivach. In order to implement the study, qualitative research approach was chosen and supported by quanti-tative data questionnaire. Thematic interview was conducted as tool for qualitative information col-lection. For quantitative data gathering, a special questionnaire was developed with a help of Kivach clinic HR manager, and then distributed among higher medical personnel of the clinic. As a result, researchers managed to gather 36 responses, which represent more than 50% of personnel in Ki-vach. According to the results of the research, it was possible to see that Kivach clinic managers have im-plemented thought-out and comprehensive motivation strategies to contribute to the overall motiva-tion level of their employees. Results of quantitative survey show that employees of Kivach clinic are motivated and satisfied with their ...